A chronic high-fat diet causes sperm head alterations in C57BL/6J mice - Funes, Abi Karenina (2019)
A chronic-positive energetic balance has been directly correlated with infertility in men, but the involved mechanisms remain unknown. Herein we investigated weather in a mouse model a chronic feeding with a diet supplemented with chicken fat affects sperm head morphology. To accomplish this, we fed mice for 16 weeks with either control food (low-fat diet, LFD) or control food supplemented with 22% chicken fat (high-fat diet, HFD). At the end of the feeding regimen, we measured: redox and inflammatory changes, cholesterol accumulation in testis and analyzed testicular morphological structure and ultra-structure and liver morphology. We found that the mice fed HFD resembled some features of the human metabolic syndrome, including systemic oxidative stress and inflammation, this group showed an increment in the following parameters; central adiposity (adiposity index: 1.07 0.10 vs 2.26 0.17), dyslipidemia (total cholesterol: 153.3 2.6 vs 175.1 8.08 mg/dL), insulin resistance (indirect Insulin resistance index, TG/HDL-c: 2.94 0.33 vs 3.68 0.15) and fatty liver. Increased cholesterol content measured by filipin was found in the testicles from HFD (fluorescence intensity increase to 50%), as well as an alteration of spermiogenesis. Most remarkably, a disorganized manchette-perinuclear ring complex and an altered morphology of the sperm head were observed in the spermatozoa of HFD-fed mice. These results add new information to our understanding about the mechanisms by which systemic oxidative stress and inflammation may influence sperm-head morphology and indirectly male fertility.